Methodology of teaching bachelors of "Management in the business of design" in the discipline of "Basics of design in Fashion", demonstrated on the example of a project assignment on researching brands: "FASHION DNА". - Andreeva V. V. (A breakthrough in science: development strategies, 2021)
The article discusses the principles of interdisciplinary relations required to train the students of "Management in business of design", who specialize in the fashion industry. A description of a tested methodology of a design project on research and definition of the "DNA of fashion brands" is provided. The article substantiates the application of the project method in business education and design education, which has established itself as effective in training future specialists at different levels of professional training. This method provides the opportunity to integrate students into the creative process and motivate them to solve unconventional problems. Working on this project in a group allows students to acquire teamwork skills and get acquainted with the functioning of global manufacturers of clothing and accessories. The result of the project is a presentation in which all stages of research, analytical process.
Keywords: образовательный процесс; проект; мода; творческий процесс; инновационные образовательные технологии; междисциплинарные связи; проблемный метод; educational process; creative process; project; дизайн одежды; fashion; индустрия моды; коллекция одежды; fashion design; clothing collection; дизайн-менеджмент; исследование моды; design management; innovative educational techniques; brand DNA; interdisciplinary connections; fashion industry; problem-based method; fashion research